Analisis Ergonomi Kamar Kos Berdasarkan Standar Pedoman Perancangan Studi Kasus: Bangunan Kos di Rembang - Setiawan Wicak, Queentana Jeoty Valentcia; Tarigan, Riandy; Riyanto W, Robert (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Boarding House Buildings are a promising business, especially for owners who wish to earn passive income without having to manage or be directly involved with the workforce. However, not all boarding houses meet comfort standards. The comfort of a boarding room is influenced by various factors, primarily the facilities provided in the room. These facilities typically include a bed, desk, chair, and wardrobe. The purpose of this study is to analyze the comfort level of boarding houses based on design guideline standards. This research uses a descriptive qualitative method by collecting data from journals, literature, and studies, which are then examined to determine their alignment with design standards for room facilities in a case study of boarding houses